2018
DOI: 10.1186/s12864-018-4575-3
|View full text |Cite
|
Sign up to set email alerts
|

A circulating microRNA signature as noninvasive diagnostic and prognostic biomarkers for nonalcoholic steatohepatitis

Abstract: BackgroundNoninvasive biomarkers are urgently needed for patients with nonalcoholic steatohepatitis (NASH) to assist in diagnosis, monitoring disease progression and assessing treatment response. Recently several exploratory studies showed that circulating level of microRNA is associated with NASH and correlated with disease severity. Although these data were encouraging, the application of circulating microRNA as biomarkers for patient screening and stratification need to be further assessed under well-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 41 publications
1
30
0
1
Order By: Relevance
“…Although the mechanisms for those dietary components caused hepatic lesions have been intensely studied, lesion regression and reversal have not been systematically studied. Besides the metabolic pathways, recent studies have shown that micro RNAs, such as miR-122, miR-192, miR-21, miR-29a, miR-34a, and miR-505, are up or down regulated at disease state of NASH and may play a role in the disease progression (Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms for those dietary components caused hepatic lesions have been intensely studied, lesion regression and reversal have not been systematically studied. Besides the metabolic pathways, recent studies have shown that micro RNAs, such as miR-122, miR-192, miR-21, miR-29a, miR-34a, and miR-505, are up or down regulated at disease state of NASH and may play a role in the disease progression (Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small (18–22 nucleotides) noncoding RNA molecules that regulate the expression of hundreds of mRNAs at the posttranscriptional level through binding to target mRNA, resulting in either mRNA degradation or translational repression [ 14 , 15 ]. miRNAs are present in extracellular spaces and affect many physiological processes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Lambrecht et al as we as Jampoka et al highlighted miR-29a as an essential part in predictive algorithm for NAFLD [29,31]. Furthermore, studies using mouse model also confirmed the close involvement of miR-29a in representing the progression of NAFLD [44,73] and NASH [74,75]. A non-exhaustive list of miR-29a with altered level in liver diseases is provided in Table 3.…”
Section: Mirs As Markers In Liver Diseasementioning
confidence: 89%